Endoscopic band ligation versus hot snare resection for hyperplastic gastric polyps in cirrhotic patients - Elsabaawy, Maha; Elbahr, Osama; Edrees, Ahmed; Badr, Reda; Kamal, Ahmed; Afify, Sameh (Clinical and Experimental Hepatology, 2024)
Managing patients with liver cirrhosis and gastric hyperplastic polyps (GHPs) is challenging. Despite being the standard technique for resection of GHPs, hot snare polypectomy (HSP) is risky in the setting of coagulation disorders associated with liver cirrhosis. The aim of the study was to assess the efficacy and safety of endoscopic band ligation (EBL), compared to HSP in resecting GHPs in cirrhotic patients. One hundred consecutive adults with liver cirrhosis and sessile or pedunculated GHPs were enrolled from December 2018 to December 2020. Cases were non-blindly randomized (1 : 1) to two groups to have GHPs managed by either EBL (group I) or HSP (group II). Data of demographic, clinical, and pathological factors, hospitalization expenses and outcomes of both treatment maneuvers were collected and statistically analyzed. Upper endoscopy was repeated for all patients at 3, 6 and 12 months after treatment for recurrence detection. Between the two procedures, the mean operational time was significantly shorter in the EBL than the HSP group (15.1 ±3.80 min vs. 36.6 ±6.72 min, p < 0.001). Concerning complications, 94% of EBL cases had reported no complications compared to 78% with HSP. Bleeding occurred only with HSP (20%) with urgent need for adrenaline and/or argon plasma coagulation ( p = 0.003). Regarding cost, it was significantly lower in EBL than HSP (280 ±2.02 EGP vs. 390 ±181.8 EGP, p < 0.001). However, the recurrence rate of GHPs and number of needed sessions were not significantly different. EBL proved to be a safer, more rapid, and economic maneuver when compared to HSP on resecting GHPs in patients with liver cirrhosis.